2017
DOI: 10.3329/mh.v6i1.34062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and antibiotic susceptibility pattern of Escherichia coli in cattle on Bathan and intensive rearing system

Abstract: The aim of this longitudinal study was to verify the prevalence and antibiotic susceptibility pattern of Escherichia coli (E. coli) in cattle reared on Bathan and intensive farming system in Bangladesh. Fecal materials originated from recto anal junction (RAJ) of 100 cattle used for primary screening on MacConkey agar. The diversities among the pink color colony producing isolates on MacConkey agar were verified by conventional cultural methods and biochemical tests. Phenotypically positive E. coli isolates we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 9 publications
7
13
0
Order By: Relevance
“…Regarding the in-vitro antimicrobial susceptibility testing, the retrieved strains exhibited a remarkable resistance to penicillins, cephalosporins, and carbapenems which gave a public health alarm. The current findings nearly agreed with those reported by Shahrani 40 , Gupta 41 , and Touwendsida 42 . The uncontrolled widespread use of antibiotics in veterinary and health sectors as well as the bacterial antibiotic-resistant genes are incriminated in the development of such multidrug-resistant strains 43,44 .…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the in-vitro antimicrobial susceptibility testing, the retrieved strains exhibited a remarkable resistance to penicillins, cephalosporins, and carbapenems which gave a public health alarm. The current findings nearly agreed with those reported by Shahrani 40 , Gupta 41 , and Touwendsida 42 . The uncontrolled widespread use of antibiotics in veterinary and health sectors as well as the bacterial antibiotic-resistant genes are incriminated in the development of such multidrug-resistant strains 43,44 .…”
Section: Discussionsupporting
confidence: 92%
“…In a similar manner, high rate of E. coli was reported in cows from Jordan [24,25]. These finding is also consistent with other reports where E. coli was observed as the predominant species in healthy animals [23,26,27,28,29,30,31]. On Isolates originating from this study were shown to be multidrug resistant ( Table 1).…”
Section: Discussionsupporting
confidence: 91%
“…The BPW containing samples were overnight incubated at 37°C for enrichment. The culture was then streaked onto MacConkey agar (Oxoid, UK), and incubated at 37°C for 18–24 h. Large Target colonies were transferred to Eosin Methylene Blue (EMB) agar (Merck, India) media and incubated at 37°C for 24 h. The biochemical tests including Voges-Proskauer (VP), Methy Red (MR), and indole production tests were performed to confirm E. coli [11]. The bacteria were preserved with 15% glycerol at −80°C until use.…”
Section: Methodsmentioning
confidence: 99%